Ampliación de la distribución geográfica de Abronia oaxacae (Squamata: Anguidae) y Tantalophis discolor (Squamata: Colubridae) en el estado de Oaxaca, México - Aldape-López, César Tonatiuh; Santos-Moreno, Antonio (Instituto de Ecología, A.C., 2016)
In this paper we report new localities for Abronia oaxacae and Tantalophis discolor in a pine forest with intense management in San Pedro El Alto locality, municipality Zimatlán, in the state of Oaxaca, southwestern Mexico. These new localities extends the known range of both species.